Enhanced-mobile ubiquitous smart environment——the super state of Internet of things - Ping ZHANG; Shilin LI; Zheng HU (物联网学报)
Enhanced-mobile ubiquitous smart environment (E-MUSE) was proposed as the super state of Internet of things (IoT),which was also the evolution of mobile ubiquitous service environment (MUSE) in the epoch of IoT.E-MUSE is a mobile,ubiquitous and intelligent information environment that runs on 5G ubiquitous network and takes 5G technology as the core.The physical structure and connotation framework of E-MUSE were defined.Around IoT,cloud-fog-edge computing,artificial intelligence,etc.,the function of these new technologies in E-MUSE were discussed.Finally,some new application based on E-MUSE was discussed.